RELIGIOUS MODERATION AND SOCIAL RESILIENCE OF THE HINDU COMMUNITY IN SEMARANG CITY: A STUDY ON HARMONY IN URBAN MULTICULTURAL SOCIETY - Gunarta, I Ketut; Putrawan, I Nyoman Alit; Subagia, I Nyoman; Mo. Masrur; Putra, I Gd. Dedy Diana (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Semarang City is a major urban center in Indonesia characterized by multicultural diversity and religious heterogeneity, including Islam, Christianity, Catholicism, Hinduism, Buddhism, and Confucianism. Within this plural context, the Hindu community, although a minority, demonstrates notable social resilience and the practical application of religious moderation. This study aims to analyze how religious moderation strengthens the social resilience of the Hindu community in Semarang. Using a qualitative descriptive approach with a case study method, the research focuses on Balinese Hindu migrants and Javanese Hindus in Dusun Kongkong, Mijen District. Data were collected through participatory observation, in-depth interviews, documentation, and analysis of official reports and academic sources, and analyzed using the Miles and Huberman interactive model. The findings show that religious moderation is reflected in the application of core Hindu teachings such as Tri Hita Karana, Tat Twam Asi, and Wasudewa Kutumbhakam, which emphasize harmony, tolerance, and respect for diversity. Social resilience is strengthened through internal solidarity, cultural adaptation, interfaith dialogue, and the use of social media for education and outreach. Pura Agung Giri Natha functions as an inclusive spiritual and social space that supports interreligious interaction. This study highlights the integration of theological values with social strategies in addressing urban challenges and strengthening minority resilience. The hybrid identity of the Hindu community, combining Balinese and Javanese traditions, reflects adaptive cultural resilience. In conclusion, religious moderation serves as a practical and transformative approach in fostering social cohesion and interreligious harmony in a diverse urban society.